Current Primary Education Prospects and Skills for Improving Quality Efficiency - Marjan Smatillayevna Janbayeva; Nurjamal Jarkurganovna Umirova (Euro Asian Journal Publishing, 2024)
Reforms in the field of primary education in Uzbekistan include full informatization of the education system, revision of traditional teaching content, integration of academic subjects, effective use of innovative pedagogical technologies in teaching. requires organization on the basis of use. This, in turn, creates the need to create a single informational educational environment in an educational institution, create an information base and use it effectively, and improve educational and regulatory documents based on the integration of subjects
Keywords: primary education; integration of academic subject; information base